Studies on the chitin/chitosan binding properties of six cuticular proteins analogous to peritrophin 3 from Bombyx mori. Issue 4 (22nd April 2017) - Qu, M.; Ren, Y.; Liu, Y.; Yang, Q.
Abstract: Chitin deacetylation is required to make the cuticle rigid and compact through chitin chain crosslinking. Thus it is presumed that specialized proteins are required to bind deacetylated chitin chains together. However, deacetylated‐chitin binding proteins have not ever been reported. In a previous work, six cuticular proteins analogous to peritrophin 3 (CPAP3s) were found to be abundant in the moulting fluid of Bombyx mori . In this study, these BmCPAP3s (BmCPAP3‐A1, BmCPAP3‐A2, BmCPAP3‐B, BmCPAP3‐C, BmCPAP3‐D1 and BmCPAP3‐D2) were cloned and expressed in Escherichia coli and purified using metal‐chelating affinity chromatography. Their binding activities demonstrated that although all of the BmCPAP3s showed similar binding abilities toward crystalline chitin and colloidal chitin, they differed in their affinities toward partially and fully deacetylated chitin. Amongst them, BmCPAP3‐D1 exhibited the highest binding activity toward deacetylated chitin. The gene expression pattern of BmCPAP3‐D1 was similar to BmCPAP3‐A1 and BmCPAP3‐C at most stages except that it was dramatically upregulated at the beginning of the pupa to adult transition stage. This work is the first report of a chitin‐binding protein, BmCPAP3‐D1, which exhibits high binding affinity to deacetylated chitin.